Förolämpning mot tjänsteman som ett nytt brott? – En kritisk granskning av den föreslagna brottsrubriceringen i SOU 2024:1 - Landgren,Tova (2024)
In a report from a government inquiry, published in January 2024, a new criminal provision is proposed for inclusion in Chapter 17 of the Swedish Penal Code. The proposed offense aims to specifically address insults directed towards officials. However, there is already an offense for insults in Chapter 5, Section 3 of the Penal Code, encompassing insults directed at both officials and non-officials. In legal doctrine, it is stated that criminalization should be used as a last resort (ultima ratio). Accordingly, frameworks have been developed to assist the legislator in determining whether a behavior should be criminalized or not. A government inquiry (Straffrättsanvändningsutredningen) has presented five criteria for criminalization. The fifth criterion stipulates that criminalization should be refrained if other methods are sufficiently effective in addressing the behavior. This involves examining if an existing criminal provision covers the unwanted conduct. If so, further criminalization should be avoided. The purpose of this essay is to critically examine whether there are special reasons to introduce a new offense for insults against officials, given that such behavior is already criminalized. Additionally, it examines if the proposed offense is likely to be effective or if it merely constitutes symbolic legislation. The method applied to answer these questions is legal dogmatic. The proposal is based on the claim that the exposure of public employees to threats, violence, and harassment has increased. In the committee directive, it is claimed that insults are used by gang criminals to strengthen their position within the criminal environment. Thus, the crime is considered necessary to mark the seriousness of the issue. However, the investigation reveals that the proposed crime is not intended to expand the criminalized area and that a certain level of tolerance in the exercise of duty must be assumed. It can therefore be questioned whether the offense will be effective. The essay discusses whether the crime’s protective interest and an increase in penalty levels can constitute special reasons for further criminalization. Considering that the primary motive behind the proposal seems to be for politicians to appear decisive, the conclusion is that double criminalization is not justified.
Keywords: straffrätt; dubbla kriminaliseringar; symbollagstiftning; förolämpning